Forming a cold electron population at a weakly outgassing comet - Stephenson,P; Galand,M; Deca,J; Henri,P; Carnielli,G (2024)
The Rosetta Mission rendezvoused with comet 67P/Churyumov-Gerasimenko in August 2014 and escorted it for two years along its orbit. The Rosetta Plasma Consortium (RPC) was a suite of instruments, which observed the plasma environment at the spacecraft throughout the escort phase. The Mutual Impedance Probe (RPC/MIP; Wattieaux et al, 2020; Gilet et al., 2020) and Langmuir Probe (RPC/LAP; Engelhardt et al., 2018), both part of RPC, measured the presence of a cold electron population within the coma.Newly born electrons, generated by ionisation of the neutral gas, form a warm population within the coma at ~10eV. Ionisation is either through absorption of extreme ultraviolet photons or through collisions of energetic electrons with the neutral molecules. The cold electron population is formed by cooling the newly born, warm electrons via electron-neutral collisions. Assuming the radial outflow of electrons, the cold population was only expected at comet 67P close to perihelion, where outgassing rate from the nucleus was at its highest (Q > 1028 s-1). However, cold electrons were observed until the end of the Rosetta mission at 3.8au when the outgassing was weak (Q